2018
DOI: 10.61426/sjbcm.v5i4.994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Media on Knowledge Sharing Practices in Kenyan Universities: A Case of Strathmore University

RICHARD KHAMALI,
PROF. THAIRU (Ph.D),
R. WANJA

Abstract: The main objective of the research was to reveal the influence of social media tools on the sharing of knowledge in Kenyan universities. The research population was arrived at and evaluated using purposive sampling, while data was gathered using questionnaires. The study further adopted descriptive research design with a statistical sample of 233 students from the Faculty of Information Technology at Strathmore University. Statistical Package for the Social Sciences (SPSS) version 21 was the software used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In their study, Kolan and Dzanza (2018) observed that despite the advantages that SM offers to students and academics such as knowledge and information sharing, interaction, collaborative learning and reduced costs of accessing knowledge and information, such sites have some drawbacks including addiction and distraction of attention especially when students are addicted on the use of such platforms for non-academic matters, which may affect students' academic performance. Khamali et al (2018) affirmed that the use of SM has proved to be useful in universities for exchanging knowledge and information in Kenya and therefore it needs to be integrated in educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Kolan and Dzanza (2018) observed that despite the advantages that SM offers to students and academics such as knowledge and information sharing, interaction, collaborative learning and reduced costs of accessing knowledge and information, such sites have some drawbacks including addiction and distraction of attention especially when students are addicted on the use of such platforms for non-academic matters, which may affect students' academic performance. Khamali et al (2018) affirmed that the use of SM has proved to be useful in universities for exchanging knowledge and information in Kenya and therefore it needs to be integrated in educational settings.…”
Section: Introductionmentioning
confidence: 99%